1987
DOI: 10.1007/bf01311338
|View full text |Cite
|
Sign up to set email alerts
|

Semliki Forest virus-induced polykaryocyte formation is an ATP-dependent event

Abstract: Infection of Aedes albopictus cells with Semliki Forest virus (SFV) leads to polykaryocyte formation below pH 6.2. This syncytium formation is accompanied by a decrease of the cellular ATP level. Addition of inhibitors of oxidative phosphorylation leads to a rapid, total depletion of ATP in infected cells at pH 6 and results in an inhibition of polykaryocyte formation. However, when cells were exposed for only a few minutes to pH 6 in the presence of the inhibitors and then kept at pH 7.2, the ATP level partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…These results confirm the observation made by others [I, 3,10]. Since we have shown previously that the fusion process induced by SFV is energydependent in Aedes cells [5,6], it is reasonable to assume that this observation in BHK cells can be explained by a disturbed ATP balance. Therefore we determined the intracellular ATP level of SFV-and mock-infected BHK cells after exposure to low pH.…”
Section: Summary the Conditions Needed To Trigger Semtiki Forest Virsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm the observation made by others [I, 3,10]. Since we have shown previously that the fusion process induced by SFV is energydependent in Aedes cells [5,6], it is reasonable to assume that this observation in BHK cells can be explained by a disturbed ATP balance. Therefore we determined the intracellular ATP level of SFV-and mock-infected BHK cells after exposure to low pH.…”
Section: Summary the Conditions Needed To Trigger Semtiki Forest Virsupporting
confidence: 92%
“…The initial step is triggered by a conformational change of a surface protein, most probably a virus-coded protein [9]. Furthermore, we have demonstrated that this fusion process is energy dependent and can be blocked by ATP depleting agents [5,6].Whereas the FFWI of SFV-infected Aedes cells proceeds to completion at both pH 6 and pH 7 after a short exposure to low pH, it had been shown that it is mandatory for infected baby hamster kidney (BHK) cells to be brought …”
mentioning
confidence: 85%
“…The pH was lowered to 5.6 by adding HCl for 3 min followed by returning to pH 7.0, all at 37°C. Because SFV-induced polykaryon formation is clearly visible by light microscopy 30 min after reduction of the pH (24,35), the spread of calcein was measured at this time. All images of this study utilized a video camera (SIT 66; Dage, Michigan City, Ind.…”
Section: Figmentioning
confidence: 99%
“…The aim of this investigation was to clarify the early events in cell-cell fusion and the action of potassium cyanide an inhibitor of oxidative phosphorylation-which inhibits SFV-induced polykaryon formation [4]-on the fusion process. To this end Aedes albopictus cells [clone C 6/36, (3)] were infected with SFV.…”
mentioning
confidence: 99%
“…Potassium cyanide is an inhibitor of oxidative phosphorylation and leads to depletion of cellular ATP. For the following reasons it can be excluded that the results obtained in presence of the relative high concentration of potassium cyanide (1 raM) represent an artefact: i) polykaryon formation occurred in presence of 1 mM KCN when the drug was added 5 to 10 minutes after lowering the pH and proceeded from a microscopically invisible to a visible state (see Table 1); ii) furthermore, we have previously shown that syncytium formation of SFV infected Aedes cells takes place also in presence of 1 mM KCN if the infected cells are exposed to pH 6 for a short time only (4). Briefly, 16 hours pi SFV-infected Aedes cells were exposed for various ti~es (1, 5 and 10 minutes) to medium of pH 6 containing 1 mM KCN.…”
mentioning
confidence: 99%